1982
DOI: 10.1266/jjg.57.241
|View full text |Cite
|
Sign up to set email alerts
|

Directional selection for pulse repetition rate of the courtship sound and correlated responses occurring in several characters in Drosophila mercatorum.

Abstract: Bidirectional selection for pulse repetition rate, or interpulse interval, A5, of the A courtship sound in Drosophila mercatorum successfully resulted in the low (LRR) and the high (HRR) pulse repetition rate lines and also the control, intermediate, line (CRR) was obtained. The response to selection was asymmetrical, the change in LRR being much greater than that in HRR. The fact that the response was not large for HRR may support Ewing (1977) who estimated the minimum interpulse interval of about 10 msec for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

1985
1985
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
1
12
1
Order By: Relevance
“…This finding is different from those of studies made on the species D. melanogaster (Schilcher, 1976), D. mercatorum (Ikeda & Maruo, 1982;Manfrin et al, 1997), and some species of the subgroup repleta (Ewing & Miyan, 1986), in which two different types of sounds were found. (412.501 ± 55.63 and 306.624 ± 57.80).…”
Section: Resultscontrasting
confidence: 68%
See 2 more Smart Citations
“…This finding is different from those of studies made on the species D. melanogaster (Schilcher, 1976), D. mercatorum (Ikeda & Maruo, 1982;Manfrin et al, 1997), and some species of the subgroup repleta (Ewing & Miyan, 1986), in which two different types of sounds were found. (412.501 ± 55.63 and 306.624 ± 57.80).…”
Section: Resultscontrasting
confidence: 68%
“…These sonograms and the analysis of sound pulses permit a division of the courtship sounds into three distinct groups: 1. courtship sounds of the species D. onca, D. fascioloides, and D. ellisoni, in which each sound sequence is composed of a sequence of short pulses, followed by a trill, similar to that found in some species of the subgroup planitibia, denominated by Hoikkala et al (1994) as phrase song. In the species D. fascioloides and D. onca, the sequence of pulses is made up of four pulses, followed by a relatively long trill, while in D. ellisoni, there are only two pulses, followed by a shorter trill; 2. the type typical of the sonogram of D. rosinae, with a courtship sound formed by simple but duplicated pulses, a pattern also observed by Ewing & Miyan (1986) in some species of the repleta group; 3. a type based on the courtship sounds of the species D. moju and D. coroica, with short pulses in sequence, similar to the pulse song of D. melanogaster (Schilcher, 1976) and sound A of D. mercatorum (Ikeda & Maruo, 1982;Manfrin et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The range of values may be constrained due to asymmetrical heritabilites (indicated by artificial selection experiments in other Drosophila species which have found it more difficult to select for shorter compared to longer IPIs (Ikeda and Maruo, 1982;Ritchie and Kyriacou, 1996), or species recognition. Song analysis of two subspecies of D. pseudoobscura, D. p. pseudoobscura and the geographically isolated D. pseudoobscura bogotana, found significant differences in IPI but the range of IPIs was within the range observed in some D. p. pseudoobscura populations (Noor et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This has the advantage that male sexual traits are usually more easily and accurately measured. Six studies have revealed a genetic basis to female preference in this way including fruit flies (Ikeda and Maruo, 1982), pink bollworms (Collins and Card&, 1989b), planthoppers (De Winter, 1992), stalk-eyed flies (Wilkinson and Reillo, 1994), sticklebacks (Bakker, 1993) and guppies (Houde, 1994). We treat these cases in detail in the following section.…”
Section: Quantitative Genetic Studiesmentioning
confidence: 99%